EXAMINING THE EFFECTS OF PEER REVIEWING ON STUDENTS’ COMPETENCE IN WRITING ARGUMENTATIVE TEXT AT THE FOURTH SEMESTER OF ENGLISH DEPARTMENT OF STAIN WATAMPONE - MUSFIRAH, MUSFIRAH (DIDAKTIKA, 2018)
The research aimed at finding out (1) The effectiveness of peer reviewing in enhancing the writing competence of the students of STAIN Watampone. (2) The writing components: content, organization, vocabulary, language use, and mechanics in that are mostly affected in the use of peer reviewing technique. This research applied a quasi-experimental method to two groups. The experimental group applied peer reviewing technique while the control group applied self assessment technique. The subjects of this research were the students of the fourth semester English Department of STAIN Watampone. The sample was chosen by applying cluster random sampling technique. In collecting data, the researcher used writing test in pretest and posttest. The data that was used in the form of quantitative data in the form of test results to write argumentative text. Then the results were analyzed by T-Test and ANOVA analysis using SPSS version 20 Program. The results of the analysis of the data showed that (1) peer reviewing techniques can enhance the quality of learning outcomes and process of writing argumentative text. It was proved by the mean score of posttest of experimental group was 75.16 while mean score of post test of control group was 68.85. The mean score of posttest was higher than the mean score of pretest (75.16>68.85). (2) The writing component was most affected of the use of peer reviewing was content (M: 22.05).